2022
DOI: 10.15537/smj.2022.43.1.20210337
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in radiology

Abstract: Objectives: To assess the knowledge and perception of artificial intelligence (AI) among radiology residents across Saudi Arabia and assess their interest in learning about AI.Methods: An observational cross-sectional study carried out among radiology residents enrolled in the Saudi Board of Radiology, Saudi Arabia. An anonymized, self-administered questionnaire was distributed in April 2020 and responses were collected until July 2020.Results: A total of 154 residents filled the questionnaire. The top 3 aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 29 publications
(60 reference statements)
1
48
0
Order By: Relevance
“…In agreement with our results, these previous studies indicated low levels of AI knowledge among medical doctors and students [37][38][39][40], while dental students had moderate levels [41]. Nevertheless, as already mentioned, AI knowledge and literacy do not equal or predict AI readiness [28].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with our results, these previous studies indicated low levels of AI knowledge among medical doctors and students [37][38][39][40], while dental students had moderate levels [41]. Nevertheless, as already mentioned, AI knowledge and literacy do not equal or predict AI readiness [28].…”
Section: Resultssupporting
confidence: 92%
“…Our study investigated AI readiness among medical and dental professionals, filling a gap in previous studies investigating readiness in the health field; prior studies instead concentrated on knowledge and attitudes [37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations